The Impact Of Digital Surveillance On Privacy Rights: A Legal and Ethical Analysis - Eka Saputra; Fitri Handayani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This paper explores the implications of digital surveillance on individual privacy rights, examining the balance between national security and personal freedom. By analyzing laws and regulations on digital monitoring across various countries, the study highlights the challenges and ethical concerns associated with widespread surveillance technologies. The findings emphasize the need for stronger legal frameworks to protect privacy without compromising security.